2019
DOI: 10.1136/thoraxjnl-2019-213722
|View full text |Cite
|
Sign up to set email alerts
|

Association between particulate matter air pollution and lung cancer

Abstract: Long-term exposure to particulate matter 2.5 μm (PM2.5) air pollution is associated with an increased risk of lung cancer. However, the evidence is limited in low-income and middle-income countries. We estimated the association between the incidence of lung cancer and PM2.5 air pollution exposure in the Urban Employee Basic Medical Insurance (UEBMI) beneficiaries in China. A total of 16 483 new lung cancer cases diagnosed from 12 966 137 UEBMI beneficiaries from 36 cities between 2013 and 2016. The relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 9 publications
2
39
0
2
Order By: Relevance
“…A growing body of evidence indicates that lung cancer incidence is associated with exposure to PM 2:5 (IARC 2013;Bai et al 2020;Zhang et al 2020). The present study supports this evidence, with a statistically significant IRR of 1.19 (95% CI: 1.09, 1.30), even after conservatively adjusting for multiple comparisons (p = 0:01).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A growing body of evidence indicates that lung cancer incidence is associated with exposure to PM 2:5 (IARC 2013;Bai et al 2020;Zhang et al 2020). The present study supports this evidence, with a statistically significant IRR of 1.19 (95% CI: 1.09, 1.30), even after conservatively adjusting for multiple comparisons (p = 0:01).…”
Section: Discussionsupporting
confidence: 84%
“…Much of the epidemiological evidence to support this association, however, is based on prospective cohort studies that examined lung cancer mortality, not lung cancer incidence. Although several recent studies have used incidence data to estimate the association between PM 2:5 and lung cancer (IARC 2013;Bai et al 2020;Zhang et al 2020), further research is needed to confirm the association and examine the sensitivity of the results to modeling choices and exposure windows.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have explored the relationship between betel nuts, cigarettes, or alcohol and oral cancer, but few studies have studied the relationship between air pollution and oral cancer. PM is typically a representative indicator of air pollution [2,4]. Compared to PM10, PM2.5 can cause greater harm to human health [4].…”
Section: Discussionmentioning
confidence: 99%
“…PM is typically a representative indicator of air pollution [2,4]. Compared to PM10, PM2.5 can cause greater harm to human health [4]. PM2.5 generally penetrates the lung barrier and enters the blood system.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen cohort studies in nine European countries showed an association between residential exposure to particulate matter air pollution and the risk for lung cancer. One study using a random 5% sample of China Urban Employee Basic Medical Insurance (UEBMI) also showed the increased risk of lung cancer associated with increasing long-term PM2.5 air pollution exposure from 1 January 2010 to 31 December 2016 [1,2]. Several prospective cohort studies in North America and Europe have evaluated the effects of long-term exposure to outdoor air pollution and demonstrated associations between ambient air pollution exposure with respiratory disease, cardiovascular disease and lung cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%